Laparoscopic treatment of giant adnexal tumors during pregnancy by umbilical external abouchement. Report of cases - Sandoval Diaz, Ither (2015)
Background: Technical and medical advances in laparoscopic surgery have made feasible to extend its use to a wide variety of gynecological pathologies. Clinical conditions considered earlier as a contraindication for its use, such as pregnancy, are now susceptible to be managed securely and efficiently with this technique and maintaining all advantages. Objective: To review the experience in managing giant adnexal mass during pregnancy via laparoscopy. Design: Retrospective, descriptive study. Setting: Specialized Gynecology Service, Hospital Nacional Edgardo Rebagliati Martins (HNERM), Lima, Peru. Participants: Pregnant women with giant adnexal tumors. Interventions: Five pregnant women admitted to the Service underwent laparoscopy. Main outcome measures: Characteristics and outcome of interventions. Results: Patients’ age average was 22.8 years, gestational age average was 14.4 weeks, tumor size average was 15 cm, and average surgical time was 52 minutes. There were no post surgical complications. All pregnancies had normal outcome. Conclusions: The external abouchement technique decreases the disadvantage of increased intra-abdominal pressure by pneumoperitoneum, decreases the surgical time, and minimizes the failure of laparoscopic expertise.